Basic life science methods a laboratory manual for students and researchers - Tantray, Javeed Ahmad; Mansoor, Sheikh; Nissa, Nighat Un; Wani, Rasy Fayaz Choh (Academic Press, 2022)
"Basic Life Science Methods: A Laboratory Manual for Students and Researchers presents forty of the most executed life science assays. The authors use a consistent structure to cover the preparation, execution and analysis of data from each method. Assays include estimation of cholesterol fractions, C-Reactive Protein, Genomic DNA isolation, Agarose Gel Electrophoresis, RT-PCR, DNA solution preparation, how to design primers, and enzyme-linked immunosorbent assay (ELISA). This book provides a complete reference containing step-by-step instructions on how to run life science assays. Laboratory staff can also benefit of the book as a training resource."